Secretome MSCs restore α-Smooth Muscle Actin Protein Tissue Expression in Croton Oil-Induced Hemorrhoid Rats - Kusumo, M. Hidayat Budi; Husain, Sofian Azalia; Amalina, Nur Dina (Stem Cell and Cancer Research (SCCR), 2023)
Background: Hemorrhoidal disease, a prevalent and distressing condition affecting a significant number of the population, presents a considerable challenge in both clinical management and patient quality of life. Secretome mesenchymal stem cell hypoxia (S-HMSCs) is involved in accelerated remodeling and regeneration of wound tissue, including hemorrhoids, through anti-inflammatory and anti-fibrotic molecules paracrine activities. Objective: This study aims to investigate the effect of Secretome Hypoxia MSCs (S-HMSCs) in restoring α-smooth muscle actin (α-SMA) expression in croton oil-induced hemorrhoid rats. Material and Methods: An experimental study with a post-test-only control group design was used in this study. Croton oil was administrated for inducting hemorrhoidal disease. A total of 24 male Wistar rats were divided into four groups (n=6); Sham (Healthy group); Untreated (Croton oil+NaCl 300 µL) Croton oil+S-HMSCs 150); Secretome 150 µL (Croton oil+S-HM SCs 150 µL) and Secretome 300 µL (Croton oil+S-HMSCs 300 µL). S-HMSCs were injected intraperitoneally every week for up to 4 weeks. All animals were scarified and the rectal tissue was collected for α-SMA immunohistochemical staining analysis. Results: After hemorrhoid induction, α-SMA was expressed 20% higher than Sham group, furthermore, administration of 150 µL and 300 µL of S-HMSCs may decreased by 15% and 20% α-SMA expression compared to the Untreated group, expression in croton oil-induced hemorrhoid rats.